2014
DOI: 10.1016/j.virol.2013.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Computer-aided codon-pairs deoptimization of the major envelope GP5 gene attenuates porcine reproductive and respiratory syndrome virus

Abstract: Synthetic attenuated virus engineering (SAVE) is an emerging technology that enables rapid attenuation of viruses. In this study, by using SAVE we demonstrated rapid attenuation of an arterivirus, porcine reproductive and respiratory syndrome virus (PRRSV). The major envelope GP5 gene of PRRSV was codon-pair deoptimized aided by a computer algorithm. The codon-pair deoptimized virus, designated as SAVE5 with a deoptimized GP5 gene, was successfully rescued in vitro. The SAVE5 virus replicated at a lower level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
44
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 29 publications
4
44
0
Order By: Relevance
“…1 i and C). By testing CPD of various mammalian viruses (16,(56)(57)(58)(59)(60) in tissue culture or in experimental animals, we have concluded that there is no single specific effect of CPD that can be related with certainty to observed deficiencies in viral proliferation of Min constructs.…”
Section: Discussionmentioning
confidence: 99%
“…1 i and C). By testing CPD of various mammalian viruses (16,(56)(57)(58)(59)(60) in tissue culture or in experimental animals, we have concluded that there is no single specific effect of CPD that can be related with certainty to observed deficiencies in viral proliferation of Min constructs.…”
Section: Discussionmentioning
confidence: 99%
“…Since deoptimization is due to the summation effect at each of hundreds or thousands of nucleotide mutations without changing amino acid sequences, the likelihood of reversion to virulence is expected to be reduced. Indeed, this technology has proven useful to derive attenuated strains of positive-strand RNA viruses such as poliovirus (16)(17)(18), porcine reproductive and respiratory syndrome virus (PRRSV) (29), and dengue virus (26), as well as those of negative-sense RNA viruses such as influenza virus (20), respiratory syncytial virus (24), and vesicular stomatitis virus (27).…”
Section: Discussionmentioning
confidence: 99%
“…Wild-type FMDV A12 (FMDV A12-WT) was generated from the full-length serotype A12 infectious clone pRMC35 (28). FMDV A12-P1 deopt was derived by modifying the codon pair bias in the 2,210-nucleotide (nt) complete P1-coding region using SAVE technology (19,29). The deoptimized fragment and 355-nt flanking viral sequences were synthesized by GenScript (Piscataway, NJ).…”
Section: Cellsmentioning
confidence: 99%
“…In principle, on the background of thousands of attenuating mutations, any single-site reversion should yield only a minuscule selective advantage. The most likely path to reversion imaginable under this model is the progressive accumulation of many individual mutations, providing for a slow progression of deattenuation (12)(13)(14).To date, genetic stability studies of large-scale deoptimized viruses have shown that deattenuation, indeed, seems to be low, suggesting that these viruses are genetically stable (6,8,(15)(16)(17)(18)(19)(20)(21). However, an important limitation of these studies is that the deoptimized viruses generally have not been subjected to strong selective pressure that…”
mentioning
confidence: 99%
“…To date, genetic stability studies of large-scale deoptimized viruses have shown that deattenuation, indeed, seems to be low, suggesting that these viruses are genetically stable (6,8,(15)(16)(17)(18)(19)(20)(21). However, an important limitation of these studies is that the deoptimized viruses generally have not been subjected to strong selective pressure that…”
mentioning
confidence: 99%